Perception of Country of Brand Origin and Country of Product Manufacturing Among Lithuanians and Emigrants From Lithuania - Dikčius, Vytautas; Stankevičienė, Gintarė (Organizations and Markets in Emerging Economies, 2010)
Though the issue of product country of origin has been researched by numerous researchers, due to globalization, currently consumers have more problems perceiving the country of origin than ever before. This brings marketing specialists back to the discussion of the topic once again, with emphasis on a distinction between the country of manufacturing origin and the country of brand origin. The impact of country of manufacturing and country of brand image varies from country to country under the influence of numerous impact factors, often summarized within a culture or subcultures. One type of such subcultures could be formed by immigrants, whose perceptions might include aspects of their home country combined with those of the host country. The main purpose of this paper was to evaluate the attitudes of Lithuanians who live in Lithuania (as a country of an emerging economy) and those of emigrants living in selected countries (Ireland, the United Kingdom and Finland) with regard to the importance of country of origin. Three brands were selected for the research – Panasonic, LG and BEKO, and three different cases were presented to the respondents. First, both the brand name (Panasonic) and the manufacturing country (the United Kingdom) were associated with a developed country. In the second case, country of brand origin (LG) was identified as a developed country while country of manufacture represented an emerging economy (Poland). Finally, an emerging economy of the country of brand origin (BEKO) and an emerging economy of the country of manufacturing (Turkey) were dealt with. Findings provide evidence that, in general, more developed countries had a better image as countries – manufacturers of TV sets than less developed countries (emerging economies). Analysis of opinions about country of brand origin revealed that brands from developed countries were evaluated better than those from emerging economies. In addition, analysis showed that respondents who live in an emerging economy have more positive attitude towards the surveyed brands compared with Lithuanian emigrants to developed countries. Finally, strong correlation was found between the evaluation of a brand and evaluation of the country of brand origin, while there was no correlation between evaluation of a brand and evaluation of country of manufacturing.